Insulator material for sealing contact pin and preparation method thereof
By blending and modifying polytetrafluoroethylene and polyimide, and adding compatibility agents, modified nanomaterials and fluorosilicone resins, an insulator material with excellent thermal properties, electrical insulation and creep resistance is prepared, which solves the problem of the degradation of the existing sealing pin insulating materials at high temperatures and long-term use, and meets the improvement of sealing requirements of electric vehicles.
Patent Information
- Application Number
- CN202411824265.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
AI Technical Summary
After high temperature and long-term use, the insulating materials of existing sealing pins have problems such as poor thermal performance, insufficient creep resistance, poor electrical insulation and antistatic properties, which are difficult to meet the improvement of sealing requirements of electric vehicles.
Polytetrafluoroethylene and polyimide are used for blending and modification, and compatibility agent, modified nanomaterial and fluorosilicone resin are added to prepare the insulator material through ball milling, kneading and extrusion granulation processes.
It improves the thermal properties, electrical insulation and creep resistance of the insulator materials, ensures that the sealing ring maintains a good sealing effect for a long time under high temperature conditions, and enhances the anti-static performance, which is suitable for the sealing needs of electric vehicles.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating materials, and in particular to an insulating material for sealing a pin and a preparation method thereof. Background Art
[0002] Sealed pins are components used for electrical connections, usually used to connect cables or lines in electronic devices. This type of pin can provide good sealing performance when connected, preventing dust, moisture or other foreign substances from entering the connection part, thereby protecting the electronic device from environmental factors.
[0003] In order to achieve a better sealing effect, a sealing ring is provided on the sealing pin to ensure a reliable seal during connection; at the same time, the sealing ring also needs to have excellent insulation and antistatic properties to avoid irreversible effects of moisture and static electricity on the stability of the electrical connection. Common sealing rings are usually made of insulating materials such as silicone, fluororubber, polyurethane, polyimide, and polytetrafluoroethylene. Although various insulating materials have excellent insulation properties, they also have certain defects to a greater or lesser extent, such as: silicone has poor solubility resistance and is prone to swelling; fluororubber will harden after long-term use; polyurethane has poor heat resistance; polyimide is more difficult to process and has a higher cost; polytetrafluoroethylene has poor plasticity, etc. All of these affect the sealing effect of the sealing ring to a certain extent.
[0004] At the same time, with the rapid popularization of electric vehicles, safety accidents have also occurred frequently. Automobile manufacturers have higher requirements for the sealing of electrical components in electric vehicles with full electrical components. For this reason, the present invention will provide an insulator material for sealing pins, which has excellent thermal performance, electrical insulation, and antistatic properties. It is prepared into a sealing ring to better meet the production needs of electric vehicles. Summary of the invention
[0005] The object of the present invention is to provide an insulating material for sealing a pin and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: An insulating material for sealing a pin comprises the following components: by weight, 60-80 parts of polytetrafluoroethylene, 20-30 parts of polyimide, 1-10 parts of a compatibilizer, 1-15 parts of a modified nanomaterial, 10-20 parts of a fluorosilicone resin, 3-5 parts of a plasticizer, and 0.2-1 parts of an antioxidant.
[0007] Furthermore, the method for preparing the insulating material comprises the following steps: Step 1: mixing maleic anhydride, isomeric decanol polyoxyethylene ether, and perfluoro n-propyl vinyl ether to initiate copolymerization to obtain a compatibilizer; Step 2: (1) pretreating molybdenum disulfide with hydrogen peroxide, and then grafting with 3-mercaptopropionic acid to obtain modified molybdenum disulfide; (2) pretreating carbon fiber with an acid solution, and then grafting with a silane coupling agent to obtain modified carbon fiber; (3) reacting the modified molybdenum disulfide with the modified carbon fiber to obtain a modified nanomaterial; Step 3: After ball milling, polytetrafluoroethylene, polyimide, compatibilizer, modified nanomaterial, fluorosilicone resin, plasticizer and antioxidant are subjected to mixing and extrusion granulation in sequence to obtain an insulating material.
[0008] Furthermore, the preparation method of the compatibilizer is: adding maleic anhydride, isomeric decanol polyoxyethylene ether, and perfluoro n-propyl vinyl ether to deionized water, stirring and mixing evenly, heating to 50-60°C, then adding dibenzoyl peroxide to initiate copolymerization, stirring the reaction for 1-5 hours, terminating the reaction, separating, and drying to obtain the compatibilizer.
[0009] Furthermore, the mass ratio of maleic anhydride, isomeric decanol polyoxyethylene ether, and perfluoro n-propyl vinyl ether is 2:(1-2):(0.5-2).
[0010] Furthermore, the amount of dibenzoyl peroxide added is 0.5-1% of the total mass of the reactants.
[0011] Both polyimide and polytetrafluoroethylene have excellent thermal properties and electrical insulation, and are often processed into insulating materials; compared with the two, polytetrafluoroethylene has poor thermal stability, but better electrical insulation, and at the same time, polytetrafluoroethylene has poor creep resistance. Therefore, the present invention is designed to use polyimide to blend and modify polytetrafluoroethylene to achieve the purpose of enhancing the thermal properties of polytetrafluoroethylene. In current research data, polytetrafluoroethylene and polyimide are usually directly blended to prepare a composite material. When the amount of a certain component added is small (1-15% by mass), it can play a certain reinforcing role. As the amount increases, the disadvantage of poor compatibility between the two becomes apparent, and the performance of the composite material begins to decline sharply. In order to obtain the best performance insulator material in the present invention, it is necessary to improve the compatibilizer of polytetrafluoroethylene and polyimide. Therefore, in the present invention, maleic anhydride, isomeric decanol polyoxyethylene ether, and perfluoro n-propyl vinyl ether are used to initiate copolymerization to prepare a compatibilizer. The compatibilizer may contain hydroxyl and fluorine, which can form an action force with the imine of polyimide and the fluorine of polytetrafluoroethylene, thereby promoting the compatibility of polytetrafluoroethylene and polyimide. That is, after adding the compatibilizer, the obtained insulator material not only has excellent thermal performance and electrical insulation, but also has good creep resistance, can maintain a good sealing effect for a long time, and can better meet the needs of practical applications.
[0012] Furthermore, the preparation method of the modified nanomaterial is as follows: (1) at room temperature, add molybdenum disulfide to a 2-5 mol / L hydrogen peroxide solution, ultrasonically treat for 5-20 minutes, let stand for 2-12 hours, and finally filter and collect the precipitate, wash and dry it to obtain pretreated molybdenum disulfide; (2) at room temperature, add the pretreated molybdenum disulfide and 3-mercaptopropionic acid to deionized water, react under ultrasonication for 2-24 hours, terminate the reaction, and freeze-dry to obtain modified molybdenum disulfide; (3) immerse the carbon fiber in an acid solution and soak it at 70-85°C for 1 hour. ~5h later, filtered, washed and dried to obtain pretreated carbon fiber; (4) adding the pretreated carbon fiber to an ethanol solution of a silane coupling agent, stirring at 40-60°C for 1-10h, filtered, washed and dried to obtain modified carbon fiber; (5) adding modified molybdenum disulfide and modified carbon fiber to anhydrous ethanol, ultrasonically treated for 5-20min, adding 4-dimethylaminopyridine and N,N'-dicyclohexylcarboximide, stirring at 5-20°C for 2-48h, ending the reaction, filtering, washing and drying to obtain modified nanomaterials.
[0013] Furthermore, the ratio of the molybdenum disulfide to the hydrogen peroxide solution is 1 g:50 mL.
[0014] Furthermore, the mass ratio of the pretreated molybdenum disulfide and 3-mercaptopropionic acid is (1~2):1.
[0015] Furthermore, the ratio of the carbon fiber to the acid solution is 1 g:10 mL.
[0016] Furthermore, the acid solution is obtained by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3.
[0017] Furthermore, the mass ratio of the pretreated carbon fiber to the silane coupling agent is 20:(1~2).
[0018] Furthermore, the silane coupling agent includes but is not limited to any one of KH-550, WD-56, and KH-791.
[0019] Furthermore, the mass ratio of the modified molybdenum disulfide, the modified carbon fiber, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbocyanine is (5-10):10:(1-3):(1-3).
[0020] Molybdenum disulfide has excellent self-lubricating properties, and thus can reduce the friction coefficient between different polymer materials, effectively avoid the generation of static electricity inside the insulating material, and make the insulator show a good antistatic effect. Therefore, the present invention is designed to introduce molybdenum disulfide into the raw material components, but the traditional molybdenum disulfide has poor dispersibility in the polymer material, and needs to be modified to enhance its dispersibility in the polymer material to achieve a better modification effect. In the scheme, molybdenum disulfide is first etched with hydrogen peroxide to cause vacancy defects in the sulfur atoms of molybdenum disulfide, and then 3-mercaptopropionic acid is inserted into the vacancy with the assistance of ultrasound to obtain modified molybdenum disulfide with a carboxyl group. In order to further improve the antistatic and thermal properties of the insulator, the scheme designs the introduction of carbon fibers to modify the insulator material, so the carbon fibers are then oxidized with an acid solution to increase the active groups (hydroxyl, carboxyl and other active oxidation groups) on their surface, and then grafted with a silane coupling agent to obtain modified carbon fibers with amino groups. Finally, the modified molybdenum disulfide and the modified carbon fibers undergo an amidation reaction to prepare a modified nanomaterial. The modified nanomaterial has more active groups because the carbon fiber is pre-treated by oxidation. The active groups that are not completely reacted can subsequently form hydrogen bonds with the fluorine on the polytetrafluoroethylene and the imine on the polyimide. Therefore, the modified nanomaterial can not only promote the compatibility of polytetrafluoroethylene and polyimide, but also has good compatibility in the polymer material itself, and can be evenly dispersed in the polymer material, so that the prepared insulating material has uniform and stable performance. In addition, under the synergistic effect of molybdenum disulfide and carbon fiber, the insulating material exhibits relatively excellent antistatic and thermal properties.
[0021] Furthermore, the plasticizer includes but is not limited to any one of triethyl acetyl citrate, chlorinated paraffin, and camphor.
[0022] Furthermore, the fluorosilicone resin includes but is not limited to any one of RF-901 fluorosilicone resin, RF-902 fluorosilicone resin, and KX-501 fluorosilicone resin.
[0023] Plasticizers and fluorosilicone resins can further improve the processability of the insulation material, and fluorosilicone resins can also improve the compatibility of polytetrafluoroethylene and polyimide to a certain extent.
[0024] Furthermore, the parameters of the ball milling treatment are: rotation speed: 100~200r / min, ball milling time: 12~24h.
[0025] Furthermore, the mixing parameters are: temperature: 180-200° C., mixing time: 0.5-1 h.
[0026] Furthermore, the extrusion granulation parameters are: temperature: 280~320℃.
[0027] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The present invention uses polyimide and polytetrafluoroethylene for blending and modification, and adds a compatibilizer to promote the compatibility of the two polymer materials, so that the insulating material has better thermal properties, electrical insulation and creep resistance; (2) The present invention obtains a modified nanomaterial by modifying and grafting molybdenum disulfide and carbon fiber. The modified nanomaterial can impart antistatic properties to the insulating material and improve the thermal properties of the insulating material. (3) After it is made into a sealing ring, its excellent thermal performance and creep resistance can prevent the deformation of the sealing ring caused by factors such as temperature, which leads to a decrease in sealing performance; its excellent electrical insulation and antistatic properties can better protect electronic equipment and prevent short circuits in electronic equipment; ultimately, it can protect the electronic equipment inside electric vehicles and thus ensure the safety of life and property. DETAILED DESCRIPTION
[0028] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0029] Embodiment 1: A method for preparing an insulating material for sealing a pin: Step 1: Prepare a compatibilizer: add 6 parts of maleic anhydride, 4.5 parts of isomeric decanol polyoxyethylene ether, and 3.2 parts of perfluoro n-propyl vinyl ether into deionized water, stir and mix evenly, heat to 50-60°C, then add 0.11 parts of dibenzoyl peroxide to initiate copolymerization, stir and react for 3 hours, terminate the reaction, separate and dry to obtain a compatibilizer; Step 2: Preparation of modified nanomaterials: (1) At room temperature (25°C), add molybdenum disulfide to a 5 mol / L hydrogen peroxide solution, wherein the ratio of molybdenum disulfide to hydrogen peroxide solution is 1 g:50 mL. After ultrasonic treatment for 10 min, let stand for 10 h, and finally filter and collect the precipitate, wash and dry it to obtain pretreated molybdenum disulfide; (2) At room temperature, add 10 parts of pretreated molybdenum disulfide and 6.5 parts of 3-mercaptopropionic acid to deionized water, react under ultrasonication for 24 h, terminate the reaction, and freeze-dry to obtain modified molybdenum disulfide; (3) Immerse the carbon fiber in an acid solution (the acid solution is a mixture of 67 wt% concentrated nitric acid and 98 wt% concentrated sulfuric acid in a volume ratio of 1:3), wherein the carbon fiber The ratio of fiber to acid solution is 1g:10mL. After soaking at 75℃ for 4h, the mixture is filtered, washed and dried to obtain pretreated carbon fiber; (4) 10 parts of pretreated carbon fiber are added to 15 parts of K-550 ethanol solution (K-550 accounts for 5wt% in the K-550 ethanol solution), stirred at 50℃ for 10h, filtered, washed and dried to obtain modified carbon fiber; (5) 8 parts of modified molybdenum disulfide and 10 parts of modified carbon fiber are added to anhydrous ethanol, ultrasonically treated for 10min, 2 parts of 4-dimethylaminopyridine and 2 parts of N,N'-dicyclohexylcarboximide are added, stirred at 10℃ for 48h, the reaction is terminated, filtered, washed and dried to obtain modified nanomaterials; Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 8 parts of compatibilizer, 12 parts of modified nanomaterial, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0030] Embodiment 2: A method for preparing an insulating material for sealing a pin: Step 1: Prepare a compatibilizer: add 6 parts of maleic anhydride, 3 parts of isomeric decanol polyoxyethylene ether, and 1.5 parts of perfluoro n-propyl vinyl ether into deionized water, stir and mix evenly, heat to 50-60°C, then add 0.08 parts of dibenzoyl peroxide to initiate copolymerization, stir and react for 3 hours, terminate the reaction, separate and dry to obtain a compatibilizer; Step 2: Preparation of modified nanomaterials: (1) At room temperature (25°C), add molybdenum disulfide to a 2 mol / L hydrogen peroxide solution, wherein the ratio of molybdenum disulfide to hydrogen peroxide solution is 1 g:50 mL, ultrasonically treat for 10 min, let stand for 10 h, and finally filter and collect the precipitate, wash and dry it to obtain pretreated molybdenum disulfide; (2) At room temperature, add 10 parts of pretreated molybdenum disulfide and 5 parts of 3-mercaptopropionic acid to deionized water, react under ultrasound for 24 h, terminate the reaction, and freeze-dry to obtain modified molybdenum disulfide; (3) Immerse the carbon fiber in an acid solution (the acid solution is a mixture of 67 wt% concentrated nitric acid and 98 wt% concentrated sulfuric acid in a volume ratio of 1:3), wherein the carbon fiber The ratio of fiber to acid solution is 1g:10mL. After soaking at 75℃ for 1h, the mixture is filtered, washed and dried to obtain pretreated carbon fiber; (4) 10 parts of pretreated carbon fiber are added to 10 parts of K-550 ethanol solution (K-550 accounts for 5wt% in the K-550 ethanol solution), stirred at 50℃ for 1h, filtered, washed and dried to obtain modified carbon fiber; (5) 5 parts of modified molybdenum disulfide and 10 parts of modified carbon fiber are added to anhydrous ethanol, ultrasonically treated for 10min, 2 parts of 4-dimethylaminopyridine and 2 parts of N,N'-dicyclohexylcarboximide are added, stirred at 10℃ for 48h, the reaction is terminated, filtered, washed and dried to obtain modified nanomaterials; Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 8 parts of compatibilizer, 12 parts of modified nanomaterial, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0031] Embodiment 3: A method for preparing an insulating material for sealing a pin: Step 1: Prepare a compatibilizer: add 6 parts of maleic anhydride, 6 parts of isomeric decanol polyoxyethylene ether, and 6 parts of perfluoro n-propyl vinyl ether into deionized water, stir and mix evenly, heat to 50-60°C, then add 0.14 parts of dibenzoyl peroxide to initiate copolymerization, stir and react for 3 hours, terminate the reaction, separate and dry to obtain a compatibilizer; Step 2: Preparation of modified nanomaterials: (1) At room temperature (25°C), add molybdenum disulfide to a 5 mol / L hydrogen peroxide solution, wherein the ratio of molybdenum disulfide to hydrogen peroxide solution is 1 g:50 mL, ultrasonically treat for 10 min, let stand for 10 h, and finally filter and collect the precipitate, wash and dry it to obtain pretreated molybdenum disulfide; (2) At room temperature, add 10 parts of pretreated molybdenum disulfide and 10 parts of 3-mercaptopropionic acid to deionized water, react under ultrasound for 24 h, terminate the reaction, and freeze-dry to obtain modified molybdenum disulfide; (3) Immerse carbon fiber in an acid solution (the acid solution is a mixture of 67 wt% concentrated nitric acid and 98 wt% concentrated sulfuric acid in a volume ratio of 1:3), wherein the carbon fiber The ratio of vitamin A solution is 1g:10mL. After soaking at 75℃ for 4h, the mixture is filtered, washed and dried to obtain pretreated carbon fiber; (4) 10 parts of pretreated carbon fiber are added to 20 parts of K-550 ethanol solution (K-550 accounts for 5wt% in the K-550 ethanol solution), stirred at 50℃ for 10h, filtered, washed and dried to obtain modified carbon fiber; (5) 10 parts of modified molybdenum disulfide and 10 parts of modified carbon fiber are added to anhydrous ethanol, ultrasonically treated for 10min, 2 parts of 4-dimethylaminopyridine and 2 parts of N,N'-dicyclohexylcarboximide are added, stirred at 10℃ for 48h, the reaction is terminated, filtered, washed and dried to obtain modified nanomaterials; Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 8 parts of compatibilizer, 12 parts of modified nanomaterial, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0032] Based on Example 1, a control experiment is carried out, and comparative examples 1 to 4 are set as follows: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: no compatibilizer is added, and other processes remain unchanged, specifically: Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 12 parts of modified nanomaterials, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125 r / min for 18 hours; then add to an internal mixer and mix at 190°C for 1 hour; finally, extrude and granulate at 300°C to obtain an insulating material.
[0033] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: no modified nanomaterial is added, and other processes remain unchanged, specifically: Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 8 parts of compatibilizer, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0034] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustments: no carbon fiber is introduced into the modified nanomaterial, modified molybdenum disulfide is used as the modified nanomaterial, and other processes remain unchanged, specifically: Step 2: Preparation of modified nanomaterials: (1) At room temperature (25°C), add molybdenum disulfide to a 5 mol / L hydrogen peroxide solution, wherein the ratio of molybdenum disulfide to hydrogen peroxide solution is 1 g:50 mL, ultrasonically treat for 10 min, let stand for 10 h, and finally filter and collect the precipitate, wash and dry it to obtain pretreated molybdenum disulfide; (2) At room temperature, add 10 parts of pretreated molybdenum disulfide and 6.5 parts of 3-mercaptopropionic acid to deionized water, react under ultrasonication for 24 h, terminate the reaction, and freeze-dry to obtain modified molybdenum disulfide; Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 8 parts of compatibilizer, 12 parts of modified molybdenum disulfide, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0035] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: no compatibilizer and modified nanomaterial are added, and other processes remain unchanged, specifically: Step 3: Add 74 parts of polytetrafluoroethylene, 22 parts of polyimide, 15 parts of RF-901 fluorosilicone resin, 4 parts of triethyl acetyl citrate, and 0.5 parts of antioxidant 1010 into a ball mill, and ball mill at a speed of 125r / min for 18h; then add to an internal mixer and mix at 190°C for 1h; finally, extrude and granulate at 300°C to obtain an insulating material.
[0036] In the above embodiments, all raw materials are from the following sources: maleic anhydride purity 99%, polytetrafluoroethylene purity 99%, purchased from Shanghai Jinjinle Industrial Co., Ltd.; isomeric decanol polyoxyethylene ether purity 99%, CAS No.: 61827-42-7, molybdenum disulfide purity 99%, 3-mercaptopropionic acid purity 99%, carbon fiber diameter 5~8μm, aspect ratio 5~20, KH-550 purity 99.5%, acetyl citrate triethyl purity 99%, CAS No.: 77-89-4, polyimide purity 99%, item No.: 62929-02-6, antioxidant 1010, all purchased from Hubei Yongkuo Technology Co., Ltd.; perfluoro n-propyl vinyl ether purity 99%, CAS No.: 1623-05-8, purchased from Shanghai Biyang Industrial Co., Ltd.; RF-901 fluorosilicone resin, purchased from Fuxin Ruifeng Fluorine Chemical Co., Ltd.
[0037] Performance testing: After the insulator materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were uniformly processed into test pieces of 10 cm in length × 5 cm in width × 3 cm in height, mechanical properties, thermal properties, insulation properties, and antistatic properties were tested. The specific test methods are as follows: 1. Mechanical properties test: According to the test method in GB / T 1040.1-2018, the tensile strength is tested to characterize the mechanical properties; 2. Thermal performance test: After aging treatment in hot air at 125°C for 168 hours, the tensile strength is tested and compared with that before aging treatment to characterize the thermal performance; 3. Insulation performance test: According to the test method in ASTM D149, test its breakdown voltage to characterize the insulation performance; 4. Antistatic performance test: According to the test method in ASTM D257, the volume resistivity is tested to characterize the antistatic performance.
[0038] The specific test results are shown in Table 1 below: Table 1
[0039] Result analysis: According to the data in Table 1 above, by comparing Example 1 with Comparative Examples 1 to 4, it can be seen that the mechanical properties, thermal properties, electrical insulation properties and antistatic properties of the insulating material prepared by the present invention are significantly improved through the synergistic effect of the compatibilizer and the modified nanomaterial, and both are indispensable.
[0040] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing an insulating material for sealing a pin, characterized in that: The following steps are involved: Step 1: maleic anhydride, isomeric decanol polyoxyethylene ether, and perfluoro n-propyl vinyl ether are mixed to initiate copolymerization to prepare a compatibilizer; Step 2: (1) pretreating molybdenum disulfide with hydrogen peroxide, and then grafting with 3-mercaptopropionic acid to obtain modified molybdenum disulfide; (2) pretreating carbon fiber with an acid solution, and then grafting with a silane coupling agent to obtain modified carbon fiber; (3) reacting modified molybdenum disulfide with modified carbon fiber to obtain modified nanomaterials; Step 3: After ball milling, polytetrafluoroethylene, polyimide, compatibilizer, modified nanomaterial, fluorosilicone resin, plasticizer and antioxidant are subjected to mixing and extrusion granulation in sequence to obtain an insulating material.
2. The method for preparing an insulating material for sealing a pin according to claim 1, characterized in that: The preparation method of the compatibilizer is as follows: maleic anhydride, isomeric decanol polyoxyethylene ether and perfluoro n-propyl vinyl ether are added into deionized water, stirred and mixed evenly, heated to 50-60° C., then dibenzoyl peroxide is added to initiate copolymerization, stirred and reacted for 1-5 hours, the reaction was terminated, and the compatibilizer was obtained through separation and drying.
3. The method for preparing an insulating material for sealing a pin according to claim 2, characterized in that: The mass ratio of maleic anhydride, isomeric decanol polyoxyethylene ether and perfluoro n-propyl vinyl ether is 2:(1-2):(0.5-2); the amount of dibenzoyl peroxide added is 0.5-1% of the total mass of the reactants.
4. The method for preparing an insulating material for sealing a pin according to claim 1, characterized in that: The preparation method of the modified nanomaterial is as follows: (1) at room temperature, adding molybdenum disulfide to a 2-5 mol / L hydrogen peroxide solution, ultrasonically treating for 5-20 minutes, standing for 2-12 hours, and finally filtering and collecting the precipitate, washing and drying it to obtain pretreated molybdenum disulfide; (2) at room temperature, adding the pretreated molybdenum disulfide and 3-mercaptopropionic acid to deionized water, reacting under ultrasonication for 2-24 hours, terminating the reaction, and freeze-drying to obtain modified molybdenum disulfide; (3) immersing carbon fiber in an acid solution, soaking at 70-85°C for 1-5 hours, filtering, washing, and drying to obtain pretreated carbon fiber; (4) adding the pretreated carbon fiber to an ethanol solution of a silane coupling agent, stirring at 40-60°C for 1-10 hours, filtering, washing, and drying to obtain modified carbon fiber; (5) Add modified molybdenum disulfide and modified carbon fiber to anhydrous ethanol, and after ultrasonic treatment for 5 to 20 minutes, add 4-dimethylaminopyridine and N,N'-dicyclohexylcarboximide, and stir the reaction at 5 to 20°C for 2 to 48 hours. End the reaction, filter, wash and dry to obtain the modified nanomaterial.
5. The method for preparing an insulating material for sealing a pin according to claim 4, characterized in that: The ratio of the molybdenum disulfide to the hydrogen peroxide solution is 1g:50mL; the mass ratio of the pretreated molybdenum disulfide to 3-mercaptopropionic acid is (1-2):1; the ratio of the carbon fiber to the acid solution is 1g:10mL; the acid solution is a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3; the mass ratio of the pretreated carbon fiber to the silane coupling agent is 20:(1-2); the silane coupling agent includes any one of KH-550, WD-56, and KH-791; the mass ratio of the modified molybdenum disulfide, modified carbon fiber, 4-dimethylaminopyridine and N,N'-dicyclohexylcarboximide is (5-10):10:(1-3):(1-3).
6. The method for preparing an insulating material for sealing a pin according to claim 1, characterized in that: The plasticizer includes any one of acetyl citrate triethyl, chlorinated paraffin, and camphor; the fluorosilicone resin includes any one of RF-901 fluorosilicone resin, RF-902 fluorosilicone resin, and KX-501 fluorosilicone resin.
7. The method for preparing an insulating material for sealing a pin according to claim 1, characterized in that: The parameters of the ball milling treatment are: rotation speed: 100~200r / min, ball milling time: 12~24h; the parameters of the mixing: temperature: 180~200℃, mixing time: 0.5~1h; the parameters of the extrusion granulation: temperature: 280~320℃.
8. The insulating material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises the following components: by weight, 60-80 parts of polytetrafluoroethylene, 20-30 parts of polyimide, 1-10 parts of compatibilizer, 1-15 parts of modified nanomaterial, 10-20 parts of fluorosilicone resin, 3-5 parts of plasticizer and 0.2-1 parts of antioxidant.